1990
DOI: 10.1002/jcla.1860040204
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the metacestode of taenia solium in the saliva from patients with neurocysticercosis

Abstract: IgG antibodies to antigens of Taenia solium metacestodes were detected in saliva samples from patients with intracerebral cysticercosis by means of an enzyme-linked immunosorbent assay (ELISA). When compared for IgG antibody activity, saliva samples from patients with various nonparasitic neurological disorders and from clinically healthy individuals yielded significantly lower (p less than 0.001) absorbance values than saliva samples from patients with neurocysticercosis. However, no differences were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
6
1
1
Order By: Relevance
“…Kunz et al 24 , detected antibodies in the 14 serum samples analyzed by ELISA with antigen of vesicular fluid from T. cracisseps and T. solium, with higher reading intensity with T. solium antigen, similar to our results (Fig 1). Otherwise, other authors reported higher sensitivity than us for IgG detection in saliva samples 25,26 .…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Kunz et al 24 , detected antibodies in the 14 serum samples analyzed by ELISA with antigen of vesicular fluid from T. cracisseps and T. solium, with higher reading intensity with T. solium antigen, similar to our results (Fig 1). Otherwise, other authors reported higher sensitivity than us for IgG detection in saliva samples 25,26 .…”
Section: Discussioncontrasting
confidence: 74%
“…These discordant results reinforce the heterogeneity of the humoral immune response involved in the parasite-host interaction in NC. Acosta 26 did not find any difference in IgA detection in saliva samples between the group of patients with NC, the control group and the group with other neurological disorders by ELISA with T. solium total antigen. Although we used the Tcra antigen, we also did not find significant differences among the groups in CSF, serum or saliva samples (p <0.001).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Stroehle et al [136] showed that specific anti- T. gondii salivary IgG concentration can be used for the diagnosis of toxoplasmosis disease. Besides that, IgG antibodies to Ags of Taenia solium metacestodes infection can also be detected in saliva samples of intracerebral cysticercosis patients, thus making it useful for the diagnosis of neurocysticercosis disease [137]. …”
Section: Salivary Antibodiesmentioning
confidence: 99%
“…In this context, an increasing number of reports dealing with salivary diagnostic tests have been published (12)(13)(14). Saliva is a more accessible fluid and easy to collect, which makes it a very attractive noninvasive procedure.…”
Section: Discussionmentioning
confidence: 99%